2015
DOI: 10.1016/j.tsf.2015.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Thin films of PtAl2 and AuAl2 by solid-state reactive synthesis

Abstract: The intermetallic compounds AuAl 2 and PtAl 2 are colored purple and yellow respectively. In the past they have been prepared by bulk melting techniques or by co-deposition in a magnetron sputterer. Here, however, we investigate films of AuAl 2 , PtAl 2 and (Au,Pt)Al 2 prepared by sequential physical vapor deposition of the elements, followed by in situ solid-state reaction. The microstructure, dielectric functions, optical properties and thermal stability of the resulting films are characterized and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(27 reference statements)
2
4
0
Order By: Relevance
“…As mentioned, XRD analysis suggested that annealing of the solar absorber above 220 °C causes diffusion of Al atoms from the substrate into the Au/AlN cermet where the Al reacts with the Au nanoparticles to form AuAl­ 2 . This is in approximate agreement with previous studies which have found the formation of well‐crystallized AuAl 2 to occur after annealing at 250 °C or greater …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…As mentioned, XRD analysis suggested that annealing of the solar absorber above 220 °C causes diffusion of Al atoms from the substrate into the Au/AlN cermet where the Al reacts with the Au nanoparticles to form AuAl­ 2 . This is in approximate agreement with previous studies which have found the formation of well‐crystallized AuAl 2 to occur after annealing at 250 °C or greater …”
Section: Resultssupporting
confidence: 93%
“…This is probably linked to the mobility of both Al and Au on the substrate and is in agreement with our previous experience that poorly crystallized or defective AuAl 2 can be deposited by magnetron sputtering at room temperature . Formation of the well‐crystallized AuAl 2 that is detectable by XRD will occur once the deposit is annealed at higher temperatures …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…However, these materials do not possess surface plasmon resonances in the low-energy half of the visible spectrum (1.6 eV -2.4 eV), which is quite rare. Among metals, only AuAl2 and its analogs, including AuGa2, AuIn2 [16], and PtAl2 [24,25] support SP resonances in this range, which makes an investigation of their plasmonic properties of interest.…”
mentioning
confidence: 99%